The impact of enterprise digital management on manufacturing: Xiaomi Auto - HUANG, ZITAO; Waworuntu, Stephanus Remond (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
In today's global business environment, digital technologies have become crucial for fostering partnerships and creating value connections. The continuous emergence of new digital technologies is reshaping business processes, presenting both challenges and opportunities in a dynamic and competitive market.Companies are navigating a changing landscape marked by technological advancements and evolving consumer preferences, with a notable shift towards personalized products. This shift necessitates flexible production models capable of accommodating diverse products and smaller batch sizes.This paper aims to explore the profound impact of enterprise digital management on the manufacturing industry, with Xiaomi Auto as a case study for indepth analysis. With the rapid development of digital technology, enterprise digital management has become one of the key strategies for the transformation and upgrading of the manufacturing industry. Firstly, the background and significance of digital management in manufacturing are introduced, emphasizing the pivotal role of digital technology in enhancing production efficiency, optimizing supply chains, improving product quality, and meeting market demands. Subsequently, through a comprehensive analysis of Xiaomi Auto digital management practices, the specific effects of digital management on production manufacturing, supply chain coordination, quality management, and marketing are discussed, along with the implementation pathways. Furthermore, the unique characteristics and successful experiences of digital management in Xiaomi Auto are summarized, providing insights and lessons learned for other manufacturing enterprises to emulate. Lastly, the paper anticipates the future trends of digital management in the manufacturing industry, including prospects for intelligent manufacturing, datadriven decisionmaking, and humanmachine collaboration, aiming to provide theoretical support and practical guidance for promoting the digital transformation and continuous innovation of the manufacturing sector.